2020
DOI: 10.3390/su12072647
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Employees’ Negative Behaviors under Abusive Supervision: A Multilevel Insight

Abstract: This study attempts to advance the current research debate on corporate social responsibility (CSR) at the micro-level by empirically examining the effect of perceived CSR on employee behaviors such as turnover intention and workplace deviance with the mediation mechanism of organizational identification. The boundary condition of group-level abusive supervision also enhances the novelty of this research. Social identity theory is used for hypotheses development. Multilevel data is collected from 410 middle ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 59 publications
6
41
0
3
Order By: Relevance
“…Secondly, the effect of firm-level perceived CSR and CSR disclosure on employees' organizational identification was also examined. This research's findings are consistent with the existing literature regarding the relationship of perceived CSR and organizational identification (Brammer et al, 2015;John et al, 2019;Mahmood et al, 2020a). However, the research did not find any research to date investigating the effect of firms' CSR disclosure on organizational identification.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Secondly, the effect of firm-level perceived CSR and CSR disclosure on employees' organizational identification was also examined. This research's findings are consistent with the existing literature regarding the relationship of perceived CSR and organizational identification (Brammer et al, 2015;John et al, 2019;Mahmood et al, 2020a). However, the research did not find any research to date investigating the effect of firms' CSR disclosure on organizational identification.…”
Section: Discussionsupporting
confidence: 87%
“…Existing research underpins the social identity theory to explain employee-organization processes. Such as understanding the employees' behaviors (Jones et al, 2019;Scheepers & Ellemers, 2019;Wang et al, 2017); testing the mechanism through which perceived CSR is linked with employees' pro-environmental behaviors ; establishing the effect of perceived CSR to minimize the negative employee behavior with the mediation of organizational identification (Mahmood et al, 2020a), and testing the positive impact of perceived CSR on employee creative performance (Abdullah et al, 2017;Brammer et al, 2015).…”
Section: Social Identity Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to validate and support the aggregation of individual-level responses of ethical leadership at a group level, this study estimated the intraclass correlation (ICC) and Rwg (j) values by following the existing literature [ 76 ]. The values were found to be within the acceptable range (ICC1 = 0.30, ICC2 = 0.42 and Rwg (j) = 0.70), validating the aggregation accompanied in this research and were consistent with the existing literature that has also reported on this type of aggregation [ 77 , 78 , 79 , 80 ]. Further, the validity of the constructs and model fit indices were assessed by performing multi-level confirmatory factor analysis in MPlus.…”
Section: Methodssupporting
confidence: 89%
“…Sin embargo, el enfoque de la responsabilidad social corporativa en estas empresas de comunicación no debe verse desde este punto de vista ético que engloba la integridad de la información que transmiten y los compromisos con la libertad de expresión, ya que es importante considerar las actividades sociales que tienen con sus grupos de interés (Díaz Campo & Berzosa, 2020). Por ejemplo, algunas de estas organizaciones manejan injustamente algunas funciones que afectan a sus stakeholders internos, también conocidos como empleados (Witkowska, 2016), quienes frecuentemente son sometidos a largas jornadas laborales, salarios bajos y censuras a la libertad de expresión (Valarezo González & Marín Gutiérrez, 2013;Mahmood et al, 2020). Así mismo, en los medios de comunicación de países de Latinoamérica, como Perú, ha sido difícil que reconozcan a sus diversos stakeholders y no solo a la sociedad en la que se encuentran.…”
Section: Marco Teóricounclassified